1999
DOI: 10.1634/theoncologist.4-5-398
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Superior Sulcus Tumors

Abstract: Superior sulcus tumor refers to any primary lung cancer presenting with constant pain in the nerve distribution of the eighth cervical, first and second thoracic nerve roots and Horner's syndrome caused by invasion of the stellate ganglion. The pain is steady, severe, and unrelenting, involving the shoulder, the vertebral margin of the scapula and ulnar distribution of the arm to the elbow and finally to the ulnar surface of the forearm, and the small and ring fingers of the hand (Pancoast‐Tobias syndrome). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…Dartevelle and Macchiarini stated the time elapsed between the onset of Pancoast-Tobias syndrome and diagnosis is still around 6 months. 3 There was a male preponderance in our study of 95.6%, this is in agreement with other studies by Alifano et al and Martinod et al that showed male predominance 85%. 4,5 This may be explained by a higher incidence of smoking among males.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Dartevelle and Macchiarini stated the time elapsed between the onset of Pancoast-Tobias syndrome and diagnosis is still around 6 months. 3 There was a male preponderance in our study of 95.6%, this is in agreement with other studies by Alifano et al and Martinod et al that showed male predominance 85%. 4,5 This may be explained by a higher incidence of smoking among males.…”
Section: Discussionsupporting
confidence: 94%
“…They are relatively rare tumors, accounting for less than 5% of all subtypes of lung cancer 1,2 Three anatomic locations are possible for these tumors: (i) anteriorly located tumors lying anterior to the scalenus anterior muscle; (ii) tumors located between the anterior and middle scalene muscles; (iii) tumors lying posterior to the middle scalene muscle, usually located in the costovertebral groove. 3 Surgical resection is the gold standard treatment. Preoperative radiation has been part of the preoperative standard of care over the last five decades.…”
Section: Introductionmentioning
confidence: 99%
“…Even in cases of subclavian vessels infiltration, it can achieve an encouraging percentage of complete resection and acceptable percentage of morbidity and mortality (1,13). Over the last 20 years, a number of modified anterior approaches have risen to facilitate the resection of cervicothoracic tumors (5,9,14,15). In our practice, we also selected the anterior access for tumor in the anterior compartment or involving the subclavian vessels.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11,13 Iatrogenic causes account for 11% of LTN palsies; 9 posterolateral thoracotomies for apical lung tumors or cardiac congenital anomalies are known to have this complication. 1,4 About 17% of cases are idiopathic. 11 Other rare reports include hematoma secondary to anticoagulation therapy and infectious origins.…”
Section: Discussionmentioning
confidence: 99%